1988
DOI: 10.1073/pnas.85.21.8335
|View full text |Cite
|
Sign up to set email alerts
|

Polarity orientation of microtubules in hippocampal neurons: uniformity in the axon and nonuniformity in the dendrite.

Abstract: We have analyzed the polarity orientation of microtubules in the axons and dendrites of cultured rat hippocampal neurons. As previously reported of axons from other neurons, microtubules in these axons are uniform with respect to polarity; (+)-ends are directed away from the cell body toward the growth cone. In sharp contrast, microtubules in the mid-region of the dendrite, -75 Jtm from the cell body, are not of uniform polarity orientation. Roughly equal proportions of these microtubules are oriented with (+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
532
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 650 publications
(576 citation statements)
references
References 18 publications
36
532
3
Order By: Relevance
“…In axons, MTs are generally long and uniformly oriented, their plus ends distal to the cell body, whereas in dendrites MTs are much shorter and exhibit mixed polarity ( Fig. 1) (Baas et al, 1989;Baas et al, 1988;Baas et al, 1991;Burton and Paige, 1981;Heidemann et al, 1981). In neither case are MTs attached to the centrosome or any known nucleating structure.…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…In axons, MTs are generally long and uniformly oriented, their plus ends distal to the cell body, whereas in dendrites MTs are much shorter and exhibit mixed polarity ( Fig. 1) (Baas et al, 1989;Baas et al, 1988;Baas et al, 1991;Burton and Paige, 1981;Heidemann et al, 1981). In neither case are MTs attached to the centrosome or any known nucleating structure.…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…Besides this difference in microtubule-associated proteins, a difference in the polarity of the microtubules in the axon and the dendrites also exists. Baas et al [1988] have found that dendrites contain microtubules with equal numbers oriented plus ends toward the growth cone and plus ends toward the cell body; axonal microtubules are uniformly oriented with all plus ends toward the growth cone. The relationship between this organization of axonal and dendritic microtubules and their associated proteins has yet to be shown, Major questions to be answered are 1) What mechanism(s) results in the localization of tau to the axon and MAP2 to the dendrite?…”
Section: Himmler 1989mentioning
confidence: 99%
“…For example, microtubules in axons and dendrites point in opposite directions-in axons, the microtubules all have their plus ends pointed away from the cell body; in dendrites, microtubules are oriented in both directions. Initially, however, the undifferentiated neurites all have plus-end-distal axonlike microtubules; minus-end-distal microtubules are steadily added to dendrites on neurite differentiation (Baas et al 1988(Baas et al , 1989. A microtubule motor protein, CHO1/MKLP1, is responsible for this later minus-enddistal transport, and subsequent differentiation such as the dendritic predominance of golgi and ribosomes discussed above is also lost if CHO1/MKLP1 is depleted (Yu et al 2000).…”
Section: What Molecular Changes Underlie the Developmental Loss In Ramentioning
confidence: 99%